United States history. Volume 2 Through the present reconstruction - Maddox, Robert James (New York McGraw-Hill Higher Education, 2009)
Reconstruction and the Gilded age; The emergence of Modern America; From progressivism to the 1920s; From the Great depression to World War II; From the Cold War to 2007; New directions for American history
Annual editions
Keywords: United States -- Periodicals -- History; United States -- Periodicals -- Historiography; United States -- Periodicals -- Civilization; Hoa Kỳ (nước Mỹ); Lịch sử nước Mỹ